2014
DOI: 10.1111/ger.12142
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a denture base acrylic resin containing silver nanoparticles onCandida albicansadhesion and biofilm formation

Abstract: Nano-silver had antifungal activity and inhibited C. albicans biofilm formation. Antifungal activity and an inhibitory effect on adhesion and biofilm formation by denture base resin containing nano-silver were discovered, especially at a higher concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
66
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 35 publications
(56 reference statements)
4
66
1
7
Order By: Relevance
“…Some efforts have currently been made to modify the chemical composition of materials or to produce a hydrophilic layer on its surface aimed at disrupting biofilm formation (Cierech and Mierzwińska-Nastalska, 2014). A growing number of intensive studies have also been carried out to modify the chemical composition of PMMA by nanoparticles, e.g., nano-Ag (Li et al 2016) or nano-Pt (Nam, 2014). 4 Nanotechnology is one of the fastest growing areas in science and technology.…”
Section: Introductionmentioning
confidence: 99%
“…Some efforts have currently been made to modify the chemical composition of materials or to produce a hydrophilic layer on its surface aimed at disrupting biofilm formation (Cierech and Mierzwińska-Nastalska, 2014). A growing number of intensive studies have also been carried out to modify the chemical composition of PMMA by nanoparticles, e.g., nano-Ag (Li et al 2016) or nano-Pt (Nam, 2014). 4 Nanotechnology is one of the fastest growing areas in science and technology.…”
Section: Introductionmentioning
confidence: 99%
“…64 It was found that PMMA/BaTiO 3 composite is thermally stable, but its increased density affects denture retention. 59,65 Noble metals Silver (Ag) Several studies found that addition of silver NPs (AgNPs) to denture base acrylic resin displayed antifungal properties, [66][67][68][69] especially at high concentrations, 70 and acted like a latent antifungal material with low-releasing Ag + . 71 On the contrary, Wady et al 72 found that incorporating silver NPs in PMMA did not affect the adhesion of C. albicans and biofilm accumulation.…”
mentioning
confidence: 99%
“…Furthermore, silver nanoparticles interact with the exposed sulfhydryl groups in bacterial proteins, thus preventing DNA replication 14 . Therefore, many studies have incorporated silver nanoparticles into denture base resins to prevent denture stomatitis 15, 16 or into dental resins to diminish biofilm accumulation over the composite and in the restoration margins 1719 .…”
Section: Introductionmentioning
confidence: 99%